Micropropagation and callogenesis of Curcuma zedoaria Roscoe - Jeanette Inamine Miachir (Scientia Agricola, 2004)
Curcuma zedoaria Roscoe (zedoary) is a medicinal properties-bearing Zingiberaceae from which rhizomes are commercially exploited. The objective of this work was to establish an in vitro protocol for micropropagation and callogenesis of Curcuma zedoaria Roscoe as alternative to improve plant production, turning economically feasible the exploitation of its secondary metabolites which present medicinal properties. Micropropagation by using shoot apexes produced by rhizome and from in vitro plants were carried out on Murashige & Skoog medium supplemented with 2.0 mg L-1 benzyl amino purine and 30 g L-1 sucrose. Plantlets were satisfactorily acclimated to greenhouse conditions by using plastic cover for at least 10 days. Treatment with endomycorrhiza at the ex vitro transferring time was beneficial to acclimatization, improving plant growth and development. Callus induction and growth were obtained by inoculating root segments on Murashige & Skoog medium supplemented with 1.0 mg L-1 naphtalene acetic acid and incubation in the dark at 25 ± 2ºC. Cell suspension cultures were established on liquid medium of same chemical composition and same culture conditions and a growth curve was obtained. Curcuma zedoaria Roscoe (zedoaria) é uma Zingiberaceae com propriedades medicinais, da qual o rizoma é explorado comercialmente. O objetivo deste trabalho foi estabelecer um protocolo in vitro para a micropropagação e calogênese de Curcuma zedoaria Roscoe, como alternativa para melhorar a obtenção de plantas, tornando economicamente possível a exploração de seus compostos secundários que apresentam propriedades medicinais. A micropropagação usando ápices caulinares produzidos por rizoma ou por plantas cultivadas in vitro foi obtida em meio de cultura contendo os sais básicos de Murashige & Skoog suplementado com 2.0 mg L-1 de benzil amino purina e 30 g L-1 de sacarose. As plântulas obtidas foram aclimatadas em casa de vegetação utilizando-se cobertura plástica por no mínimo 10 dias. O tratamento das plântulas com endomicorrizas, no momento de transferência das plantas para casa de vegetação, foi benéfico para o processo de aclimatização, melhorando o crescimento e desenvolvimento das plantas. Calos foram obtidos pela inoculação de segmentos de raízes em meio de cultura contendo os sais básicos de Murashige & Skoog suplementado com 1.0 mg L-1 de ácido naftaleno acético e mantidos no escuro. Culturas de células em suspensão foram estabelecidas em meio líquido de mesma composição e sob as mesmas condições de cultivo e uma curva de crescimento foi estabelecida para a espécie.